2013
DOI: 10.1186/1475-2859-12-124
|View full text |Cite
|
Sign up to set email alerts
|

An improved Bacillus subtilis cell factory for producing scyllo-inositol, a promising therapeutic agent for Alzheimer’s disease

Abstract: BackgroundBacillus subtilis 168 possesses an efficient pathway to metabolize some of the stereoisomers of inositol, including myo-inositol (MI) and scyllo-inositol (SI). Previously we reported a prototype of a B. subtilis cell factory with modified inositol metabolism that converts MI into SI in the culture medium. However, it wasted half of initial 1.0% (w/v) MI, and the conversion was limited to produce only 0.4% (w/v) SI. To achieve a more efficient SI production, we attempted additional modifications.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…To solve this problem, iolABCDEFHIJ, iolX, and iolR were deleted from the chromosome using a marker-free deletion technique 6 to yield strain MYI04. 7 As expected, MI was not wasted in MYI04, but the conversion rate of MI to SI was not improved. We accordingly attempted the overexpression of iolG and iolW, which encode the key enzymes for the conversion, under the control of strong and constitutively active promoters, even during stationary growth; the promoters were chosen from global B. subtilis transcriptome analysis data.…”
Section: Cell Factorysupporting
confidence: 56%
See 1 more Smart Citation
“…To solve this problem, iolABCDEFHIJ, iolX, and iolR were deleted from the chromosome using a marker-free deletion technique 6 to yield strain MYI04. 7 As expected, MI was not wasted in MYI04, but the conversion rate of MI to SI was not improved. We accordingly attempted the overexpression of iolG and iolW, which encode the key enzymes for the conversion, under the control of strong and constitutively active promoters, even during stationary growth; the promoters were chosen from global B. subtilis transcriptome analysis data.…”
Section: Cell Factorysupporting
confidence: 56%
“…11 In the previous study, we showed that the reduction of scylloinosose catalyzed by IolW requiring NADPH could be the most important step in SI conversion and also that the reduced amounts of the major nutrient Bacto soytone drastically reduced SI conversion. 7 The results suggested that higher concentrations of Bacto soytone might stimulate NADPH regeneration. In addition, our preliminary observation suggested that inactivation of some of NADPH regenerating enzymes could result in decreased SI conversion even in the presence of higher concentrations of Bacto soytone.…”
Section: Cofactors Required For Inositol Conversionmentioning
confidence: 96%
“…As reported in a previous study, when 2% (w/v) Bacto soytone contained in the conversion medium was reduced, SI production was impaired significantly in strain KU106, although no severe effect on cell growth was observed [15]. Therefore, we tested the conversion in the medium containing a higher concentration of Bacto soytone, such as 4% (w/v), using the strains mentioned above.…”
Section: Resultsmentioning
confidence: 97%
“…Whole‐cell catalytic reactions for SI production were performed at 5 mL scale at 55 °C for 6 h in 20 m m phosphate buffer (pH 7.0) containing 20 g L −1 MI and whole cells harboring pETDuet‐ idh ‐ sidh or pETDuet‐ sidh ‐ idh with OD 600 of 20. Then a same volume of acetonitrile was added to terminate the reaction and the concentration of SI was quantified by the method described previously with slight modification (see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Compared to chemical methods, biological strategies are preferable for the synthesis of SI, even on an industrial scale, since they are environmentally benign and reaction conditions are generally mild. Bacillus subtilis cell factories were recently developed for the production of SI by modifications of inositol metabolism and culture conditions including knockout of several genes related toinositol metabolism, overexpression of key enzymes, and addition of nutrients (bacto soytone) in the medium . However, the conversion efficiency of these cell factories was limited by some factors such as metabolic factors and the efflux system of SI.…”
Section: Introductionmentioning
confidence: 99%